Students’ attitude towards online education system: A comparative study between Public and Private Universities in Bangladesh - Khadiza Benta Nasir; Meher Neger (Journal of Social, Humanity, and Education, 2022)
Purpose: This study aimed to inquire about the students’ attitude towards the online education system as well as a comparison has been made between public and private university students’ attitudes. Research methodology: The descriptive research methodology was used for this study. Data was collected from 240 students where 120 were public university students and 120 were private university students. A structured and close-ended questionnaire with a seven-point scale had been used to collect data. The sampling method was non-probability. Descriptive statistics analysis, reliability analysis, and multiple regression analysis were measured by SPSS 25.0 version. Results: The result shows that the public university students’ attitude has a positive relation to interaction, internet self-efficacy, and students’ self-determination, but has no relationship with course design and technical support. The private university students’ attitude is influenced by all factors except technical support. Limitations: This study focused only on Bangladeshi students. Contribution: This paper will assist the authority to understand the students’ attitude towards the online education system and take initiatives to make it more acceptable to the students.